Analysis of Arabic Language Learning Planning Model - Fahmi, Khairil (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
Learning planning must be prepared in a systematic way and according to the needs to  achieve the desired goal. In this case, the researcher used qualitative research in describing how the learning planning is, as for the points to be discussed, namely; (1) finding relevant data to the topic being discussed, (2) collecting and classifying data from the sources to be analyzed, (3) analyzing the advantages and disadvantages related to the data, (4) concluding the results of the analysis. The results of the analysis can be concluded that learning planning must start from external aspects such as curriculum, teaching materials and internal aspects such as learning methods, learning strategies and techniques, learning media and learning resources.